Methotical means of pedagogical interaction in the system of future music teachers preparation - N.H. Guz (Academy of Cognitive and Natural Sciences, 2006)
The article highlights new requirements regarding the organization of pedagogical interaction in the system of higher musical and pedagogical education. Methodical means are emphasized here.